Electrochemical Li/Na Intercalation in TiOSO4, First Member of the Phosphate Tungsten Bronze-Type Family. Issue 3 (1st January 2015) - Gnanavel, Muthaiyan; Raveau, Bernard; Pralong, Valerie
Abstract : The oxysulfate TiOSO4 has been prepared by an easy soft chemistry method based on the dissolution of metallic titanium in sulfuric acid at 170°C. First member of the phosphate tungsten-type bronze family, this oxysulfate, whose structure offers empty pentagonal tunnels, is shown to intercalate up to 0.9 Li per formula unit (f.u) and 0.8 Na/f.u. at an average voltage of 2.45 V vs Li + /Li and 2.12 V vs Na + /Na, respectively. The intercalation/deintercalation process is reversible according to a solid solution mechanism. Its comparison with the titanium Nasicon shows that it exhibits a similar redox voltage, but a significantly larger reversible capacity of 120 mAh/g vs Li + /Li and 100 mAh/g vs Na + /Na after 20 cycles. The open structure of this material, its low cost, and its easy synthesis, pave the way to the investigation of other transition metal oxysulfates for the realization of electrodes for rechargeable sodium ion batteries.